Fabrication and characteristics of anode as an electrolyte reservoir for molten carbonate fuel cell - Youn, Ju Young; Yoon, Sung Pil; Han, Jonghee; Nam, Suk Woo; Lim, Tae-Hoon; Hong, Seong-Ahn; Lee, Kwan Young (ELSEVIER SCIENCE BV, 2006)
In order to design the anode of a molten carbonate fuel cell (MCFC) to serve as an additional electrolyte reservoir, the surface of a conventional Ni-10 wt. % Cr anode is modified with bohemite sol by means of a dip-coating method. After coating the bohemite sol on the nickel surface, the surface layer is change into lithium aluminate particles during the course of cell operation. This results in good electrolyte wettability compared with a bare nickel surface. Consequently, the surface modification makes it possible to increase the electrolyte filling contents in the anode pores from 25-30 to 50-60 vol.%. In addition, the anti-sintering ability is induced due to the presence of lithium aluminate particles between the nickel particles. These findings show that the surface modification can increase both the structural stability and the electrolyte loading of the anode. (c) 2005 Elsevier B.V. All rights reserved.